Spirituality in film : a critical enquiry into the film Yesterday and the question of stigmatisation within the context of the HIV pandemic - Le Roux, Elisabet (Stellenbosch : Stellenbosch University, 2012)
Thesis (MTh)--Stellenbosch University, 2008.